A RETROSPECTIVE ANALYSIS OF THE INTERRELATED DEVELOPMENT OF SCIENCE AND HIGHER EDUCATION IN THE WORLD - Pozdnyakov, Andrey Leonidovich; Pozdnyakova, Ekaterina Viktorovna; Ozerova, Anna Vladimirovna (Journal of Applied Engineering Science, 2019)
The article discusses the process of forming scientific and educational centers in a historical context. Science and education have been developed in interconnection since ancient times. Changes in one area have always entailed changes in another. All these transformations were naturally reflected in the architectural and planning appearance of educational objects. Initially, universities did not have their own buildings, and classes were held in rented premises. At the same time, students and teachers tried to settle near the classrooms. Over time, this led to the formation of colleges, university complexes, campuses, and later entire university cities. When considering examples of university complexes in various cities and countries, the main fundamental components of modern scientific and educational centers were highlighted. Based on this, it was concluded that at present the university is a space of education, science and communications, the joint work of researchers, specialists and students